2024
DOI: 10.1111/pim.13053
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Regulation of Leishmania Parasite Internalisation in Macrophages and Downstream Cellular Events

Priscilla Carvalho Cabral,
Sophia K. Stegeman,
Martin Olivier
et al.

Abstract: Leishmania spp. parasites use macrophages as a host cell during infection. As a result, macrophages have a dual role: clearing the parasite as well as acting as host cells. Recently, studies have shown that macrophages harbour circadian clocks, which affect many of their functions such as phagocytosis, receptor expression and cytokine release. Interestingly, Leishmania major infection in hosts was also shown to be under circadian control. Therefore, we decided to investigate what underlies the rhythms of L. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…We previously showed that Leishmania major infection is regulated by the host circadian clock, such that parasite development, inflammation, and recruitment of innate immune cells at the site of infection, as well as the production of cytokines and chemokines, were all varying according to the time of infection ( 26 ). Interestingly, circadian rhythms were also found at the cellular level, upon infection of bone marrow–derived macrophages (BMDMs) by Leishmania parasites , and these rhythms were lost in cells lacking a functional circadian clock (lacking the essential clock gene Bmal1 ) ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that Leishmania major infection is regulated by the host circadian clock, such that parasite development, inflammation, and recruitment of innate immune cells at the site of infection, as well as the production of cytokines and chemokines, were all varying according to the time of infection ( 26 ). Interestingly, circadian rhythms were also found at the cellular level, upon infection of bone marrow–derived macrophages (BMDMs) by Leishmania parasites , and these rhythms were lost in cells lacking a functional circadian clock (lacking the essential clock gene Bmal1 ) ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%